TO EVALUATE THE RELATIONSHIP BETWEEN THYROID PROFILE AND IRON STATUS AMONG HYPOTHYROID PATIENTS - SINGH, TEJINDER; SEHGAL, GARIMA; KAUR, JASPREET; GUPTA, SANGEETA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Iron deficiency is very commonly seen among hypothyroidism patients. The study aimed to find out the relationship between thyroid profile and iron status among hypothyroidism patients, whether it is interdependent or not. Methods: This retrospective study was conducted among hypothyroidism patients at the Department of Biochemistry, Government Medical College, Amritsar. One hundred study participants were included in this study. The study participants were divided into two groups. Fifty hypothyroidism patients served as cases and 50 normal healthy individuals as control. Serum thyroid-stimulating hormone (TSH), T3, and T4 levels and serum ferritin, iron, and TIBC levels were estimated and then compared between the two groups. Results: In our findings, 70% of the females were hypothyroidism patients. Hypothyroidism patients’ mean age±SD value was 37±15.1 whereas the healthy control group was 39±12.5. Most of the middle-aged people suffer from this disease, i.e., 52%. In this study, the levels of ferritin, and iron were found to decrease whereas that of TIBC increased in patients suffering from hypothyroidism as compared to healthy controls. Serum TSH levels were inversely correlated with ferritin. The levels of ferritin were found to be significantly decreased in patients as compared to controls. Conclusion: Thyroid hormone insufficiency may lead to a deficiency of iron and vice versa. Other factors such as oxidative stress may also play a role. Thus, iron the estimation using the above parameters may be useful during diagnosing and treating hypothyroid patients.